The transcription factor Zeb2 regulates development of conventional and plasmacytoid DCs by repressing Id2 - Scott, Charlotte L. (The Rockefeller University Press, 2016)
Lambrecht et al. show that the transcription factor Zeb2 regulates commitment toward both the pDC and cDC2 lineages by repressing Id2.